MAKASSAR NAMA KOLEKTIF: Masyarakat Migran Sulawesi Selatan di Alor Kecil, Kabupaten Alor, Nusa Tenggara Timur - Abdurrahman Patji (LIPI Press, 2009)
Migration of the Bugis-Makassar people is well-known for a long time. They have migrated in many territories within the modern Indonesian state as well as to several countries in the world. This article discusses the adaptation strategy of â€œMakassarâ€ (a collectively name of South Sulawesi) migrants within the society of Alor Kecil, in the district of Alor, Nusa Tenggara Timur Province, which consisting of many ethnical groups. Some aspects to discuss regarding with adaptation process are economic activities, local politics, agricultural efforts, cultural equivalent, and kinship relationship. All those aspects contribute as push-factors to accelerating the adaptation process. The children of South Sulawesi or Makassar migrants had been acknowledged as one of eight ethnical and cultural groups and they live among them peacefully. Keywords: Migration, adaptation, Makassar people